Cervical cancer and Nursing care (Research, Society and Development, 2021)
Cervical cancer is a public health problem, being one of the most frequent causes of death among women in Brazil, with a high incidence rate. Objective: To analyze evidence on nursing care in the prevention, diagnosis and treatment of cervical cancer. Method: systematic literature review carried out in PubMed, Lilacs, BDENF, Medline (Via BVS) databases, by search strings using terms obtained from DeCS and MESH and keywords combined with Boolean operators (AND, OR, NOT). 8 articles for review. The importance of nursing care to women of any age for the prevention or early detection of gynecological cancers is evident. Conclusion: nursing professionals are essential in health education, to clarify the importance of preventive examination and early treatment. It is important to highlight the establishment of a bond with the patient to understand their needs, offering quality and humane care.